Customer Satisfaction Mediates the Relationship Between Experiential Value and Customer Engagement Behavior in Virtual Try-On Technology - Ni Putu Chantika Aprilia Nariswari; Nyoman Sri Subawa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The advancement of digital technology has encouraged e-commerce platforms to adopt interactive features such as Virtual Try-On to enhance a more visual and personalized shopping experience. This feature allows consumers to virtually try products, thereby assisting in product evaluation prior to purchase decisions. This study aims to analyze the effect of experiential value on customer engagement behavior, with customer satisfaction as a mediating variable. The research employs a quantitative approach through a survey of 150 respondents in Indonesia who have used Virtual Try-On, using a purposive sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS). The results indicate that experiential value has a positive and significant effect on both customer satisfaction and customer engagement behavior. Furthermore, customer satisfaction also has a positive effect on customer engagement behavior and partially mediates the relationship between experiential value and customer engagement behavior. These findings suggest that valuable technology-driven experiences can enhance customer satisfaction and encourage more active consumer engagement. This study contributes theoretically to the literature on digital consumer behavior and offers practical implications for e-commerce platforms in optimizing Virtual Try-On features.